Performance on a Motor Control Test in an Asymptomatic Adolescent Population - Kari Lindegren; Kristin Bastian; Christopher Kovacs; Robyn McHugh; Catherine Quatman-Yates; Mark Paterno (International Journal of Sports Physical Therapy)
# Background